Trihydroxyethyl Rutin Provides Neuroprotection in Rats With Cervical Spinal Cord Hemi-Contusion - Liu, Yapu; Liu, Qi; Yang, Zhou; Li, Rong; Huang, Zhiping; Huang, Zucheng; Liu, Junhao; Wu, Xiuhua; Lin, Junyu; Wu, Xiaoliang; Zhu, Qingan (Frontiers in Neuroscience, 2021)
Objective: To investigate the neuroprotective effects of trihydroxyethyl rutin in rats with cervical spinal cord hemi-contusion. Methods: Adult male Sprague–Dawley rats were subjected to hemi-contusion at a stroke depth of 1.2 mm, and then intraperitoneally injected with 50 or 100 mg/kg trihydroxyethyl rutin per day (T50 and T100 groups, respectively). Changes in somatosensory evoked potentials (SEPs), motor evoked potentials (MEPs), and behavior were continuously monitored. At 12 weeks post-injury, immunohistochemical staining was performed to assess changes in cervical spinal cord microvascular morphology. Magnetic resonance imaging (MRI) scans were performed to examine end-stage injury in the cervical spinal cord, and Eriochrome cyanine-stained slices of spinal cord tissue were evaluated for injury. Results: There were no significant differences in biomechanical parameters among the sham, spinal cord injury, and T50 and T100 rat groups. At 3 days-post-injury, there was a significant decrease in grip strength in all groups. At 12 weeks post-injury, grip strength recovery was significantly better in the T50 and T100 groups than in the injury group. Compared with the injury group, the total limb placement frequency was significantly higher in the T50 group at 2, 4, 6, 10, and 12 weeks post-injury and in the T100 group at 2, 6, 8, and 10 weeks post-injury. Ipsilateral SEPs and MEPs were dynamic, increasing in latency and decreasing in amplitude in the injury compared with sham group. MRI scanning demonstrated that the coronal, sagittal, and transversal lesion areas were smaller in the T50 and T100 groups than in the injury group. Microvascular density showed a greater reduction in the injury group compared with the T50 and T100 groups. Eriochrome cyanine staining showed that the ipsilateral side, residual parenchyma, and gray matter areas were larger in the T50 and T100 groups than in the injury group. Conclusion: Trihydroxyethyl rutin exhibits robust neuroprotective effects, improving limb motor function and nerve electrophysiological parameters after spinal cord injury, maintaining microvascular density, and reducing the area of injury and degree of demyelination.